Can contactless volunteer activities be an alternative during the COVID-19 pandemic? - Won, Doyeon; Chun, Yoonha; Kim, Minsuh Savina; Kim, Ian Song; Cheun, Amber Hyunjin; Lee, Alice Hyoeun; Choi, Sean Youngjae (Technium Social Sciences Journal, 2021)
The purpose of this study is to provide a viable alternative for volunteer services which became inactive due to the COVID-19 pandemic. Accordingly, cases of contactless volunteer work involving children using the M Social Welfare Center located in the city of Paju in Gyeonggi-do Province were studied using reputational case selection. The aforementioned children are children whose parents have hearing disabilities (CODAs: child of deaf adults). In all of the examined cases, six sessions of online volunteer work have been carried out with these children. In-depth interviews were conducted with four participants, two non-participants, two of the twelve youth volunteers, and one social worker. The results of the study were as follows: firstly, there are several advantages to online volunteer work such as providing an alternative to the conventional volunteering method during the COVID-19 pandemic, no restrictions of location or place, recipients having their own private space, and the volunteers and recipients being able to open up to each other and being able to grow together through this process. Secondly, issues to be noted during the process are the characteristics of the recipients, the role of social workers, the education of volunteers and the attitude of the volunteers. Finally, aspects that need to be improved are the recognition of online volunteer hours and paralleling online volunteer work with other volunteer methods when the COVID-19 situation improves in the future. Through these findings, this study suggested practical and policy implications.